Part (a)
Lets say we had the two general vectors
u = (a,b)
v = (c,d)
The dot product is
u dot v = a*c + b*d
-------------------
Apply that rule to these specific vectors
u = (5, -2)
v = (0, 1)
So we get
u dot v = 5*0 + (-2)*1
u dot v = 0 - 2
u dot v = -2
Therefore,
(u dot v)*w = -2*(-1, -3)
(u dot v)*w = ( -2*(-1), -2(-3) )
(u dot v)*w = (2, 6)
Answer: (2, 6)
=============================================
Part (b)
u = (5, -2)
5u = 5*(5, -2)
5u = (5*5, 5*(-2))
5u = (25, -10)
5u dot v = (25, -10) dot (0,1)
5u dot v = 25*0 + (-10)*1
5u dot v = 0 - 10
5u dot v = -10
Answer: -10